2008
DOI: 10.1080/17453670710014743
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient recovery of neuromuscular activity around the knee after experimental anterior cruciate ligament reconstruction

Abstract: Background Operative and nonoperative treatment of anterior cruciate ligament (ACL) injuries is often associated with a lack of proprioception and persistent muscle weakness of unknown origin.Methods This long-term study in the cat experimentally compares both neural and muscular activity in the articular nerves of the knee (PAN and MAN), quadriceps and hamstrings, in the chronic unstable knee, and in the reconstructed knee. We also investigated changes in neuromuscular response due to the mechanical competenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The outcome of such a procedure depends on two biological events that occur after the implantation–maturation of the graft and integration and secure fixation of the graft into the osseous tunnel. After implantation, the tendon graft matures by changing into a more ACL-like structure by changes in ultrastructure(3840), vascularization(41, 42), and innervation(4347). During the first two weeks after implantation there is histological evidence for central necrosis and subsequent hypocellularity in the graft, followed by a phase of vascularization and repopulation by host cells from week 4 to 10.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of such a procedure depends on two biological events that occur after the implantation–maturation of the graft and integration and secure fixation of the graft into the osseous tunnel. After implantation, the tendon graft matures by changing into a more ACL-like structure by changes in ultrastructure(3840), vascularization(41, 42), and innervation(4347). During the first two weeks after implantation there is histological evidence for central necrosis and subsequent hypocellularity in the graft, followed by a phase of vascularization and repopulation by host cells from week 4 to 10.…”
Section: Discussionmentioning
confidence: 99%
“…Existing injury incidence data in elite male youth soccer indicates that injuries occur mainly in the lower extremities (71–80%) and are largely non-contact in nature, with a high proportion of ligament sprains occurring at the ankle and knee (26, 39). Deficits in neuromuscular control and aberrant movement patterns such as cutting, turning, and landing occurring frequently during game activities, (Price et al, 2004) are suggested pathomechanics (1, 47) that underlie sport-related injury (16). …”
Section: Introductionmentioning
confidence: 99%
“…Previous research investigating the effects of age, growth and maturation on jumping tasks has shown a trend of increased performances with age (12, 37). However, variation across growth and maturation may also be evident (28, 37) and movement variability during jumping tasks is more evident in younger athletes (16). To the author’s knowledge, no data currently exists to confirm the reliability of jump-landing kinetic assessments for male youth soccer players.…”
Section: Introductionmentioning
confidence: 99%
“…3,7,15-28 Frequently occurring comorbidities such as meniscus tears further increase the risk of OA after ACL replacement, as do concomitant chondral and subchondral damages sustained during the initial trauma. 19,21-26,28 Additionally, it has been shown that even after completed ligamentization, which describes the transformation of a graft in to an ACL-like structure after implantation, there are important differences in the ultrastructure, 29-31 vascularization, 32,33 and innervation [34][35][36][37][38] between an ACL graft and a native ACL. These differences may not be critical determinants of the immediate and intermediate clinical outcome, but might contribute to degenerative processes on different levels, suggesting that a repair that retains structure, innervation, and the bone-ligament interface might be more beneficial for long-term knee health than simple replacement.…”
Section: The Clinical Problem Of Acl Rupturesmentioning
confidence: 99%